Current Research Trends of Scratch Block based Programming for K-12 : A Systematic Review - Badruliman, Batni; Syahrul Nizam, Junaini; Jonathan, Sidi; Wan Azani, Mustafa; Zamhar Iswandono, Awang Ismail (Semarak Ilmu Publishing, 2025)
In the evolving landscape of K-12 education, the introduction of programming skills through block-based environments such as Scratch has become increasingly common. This approach meets the growing need for computer literacy among students, but its effectiveness in improving learning outcomes remains controversial. The aim of this paper is to systematically review and summarize current research on the use of Scratch as a teaching and learning tool in K-12 education. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology, this paper analyses 27 relevant articles to assess the impact and use of Scratch in educational settings. The review aims to identify the current trends, methods and foci in Scratchrelated educational research. Our results show that 17 studies focus on the use of Scratch in teaching CS and ICT subjects, while 10 examine its application in other academic disciplines. The review shows generally positive results of Scratch programming in an educational context. However, it also highlights the need for more comprehensive empirical research. This includes conducting studies with larger and more diverse student samples over longer periods of time to gain a deeper understanding of how Scratch programming can effectively improve learning outcomes in K-12 education.